Anisotropic, Wrinkled, and Crack-Bridging Structure for Ultrasensitive, Highly Selective Multidirectional Strain Sensors - Zhang, Heng; Liu, Dan; Lee, Jeng‑Hun; Chen, Haomin; Kim, Eunyoung; Shen, Xi; Zheng, Qingbin; Yang, Jinglei; Kim, Jang‑Kyo (Nano-Micro Letters, 2021)
Flexible multidirectional strain sensors are crucial to accurately determining the complex strain states involved in emerging sensing applications. Although considerable efforts have been made to construct anisotropic structures for improved selective sensing capabilities, existing anisotropic sensors suffer from a trade-off between high sensitivity and high stretchability with acceptable linearity. Here, an ultrasensitive, highly selective multidirectional sensor is developed by rational design of functionally different anisotropic layers. The bilayer sensor consists of an aligned carbon nanotube (CNT) array assembled on top of a periodically wrinkled and cracked CNT–graphene oxide film. The transversely aligned CNT layer bridge the underlying longitudinal microcracks to effectively discourage their propagation even when highly stretched, leading to superior sensitivity with a gauge factor of 287.6 across a broad linear working range of up to 100% strain. The wrinkles generated through a pre-straining/releasing routine in the direction transverse to CNT alignment is responsible for exceptional selectivity of 6.3, to the benefit of accurate detection of loading directions by the multidirectional sensor. This work proposes a unique approach to leveraging the inherent merits of two cross-influential anisotropic structures to resolve the trade-off among sensitivity, selectivity, and stretchability, demonstrating promising applications in full-range, multi-axis human motion detection for wearable electronics and smart robotics. Highlights: 1 Two functionally different anisotropic layers are rationally assembled for highly selective and stretchable multidirectional strain sensors. 2 Concurrently excellent selectivity, sensitivity, stretchability, and linearity up to 100% strain is demonstrated for the first time in a multidirectional strain sensor. 3 A novel stepwise crack propagation mechanism is proposed to enable high stretchability and linearity.